(untitled) (KONFERENSIYA, 2026)
This article analyses the benefits and effectiveness of problem-based learning for improving social and communication skills, problem-solving, critical thinking skills, and self-learning skills, higher order thinking, self-directed learning skills, promotes collaboration of students and motivate teachers to teach new information. Besides this article describes developing critical thinking of students by using ploblem-based learning in classes.